SOSIALISASI NARKOBA KEPADA MASYARAKAT DESA NGADIRJO KECAMATAN SALAMAN KABUPATEN MAGELANG SEBAGAI UPAYA MENANGKAL ANCAMAN GLOBAL - Asep Kusman; Windy Kartika (JURNAL DWIJA KUSUMA, 2023)
This research focuses on the important role of village community understanding of drugs, especially in Ngadirejo Village, Salaman District, Magelang Regency. The method used in this research is descriptive qualitative. The source of the data was obtained by the researcher going directly to Ngadirejo Village by distributing questionnaires, observation and documentation. The results of this study are that first, the people of Ngadirejo Village generally do not understand the types of drugs, but the community understands the dangers of drugs to the sovereignty of the nation and state. The two people of Ngadirejo Village agree that there is a need for outreach and counseling about drugs so that environmental security in Ngadirejo Village is guaranteed, especially for families and children.